Three-dimensional fracture migration evolution law of overburden rock in steeply dipping working face - Panshi XIE; Baofa HUANG; Yongping WU; Shenghu LUO; Mingjian ZHU; Leilei YI; Hui XU; Jianjie CHEN (Meitan kexue jishu)
The key to safe and efficient mining of steeply dipping coal seam is the multi-dimensional coupling control of surrounding rock and equipment. Quantitative characterization of the spatial structure fracture characteristics of the overlying rock, the development of mining fractures, and the distribution characteristics of voids in the mining area are the prerequisites for achieving precise rock layer control in such coal seams. Based on the engineering background of steeply dipping longwall and large mining height working face, the research methods of numerical calculation, field measurement and theoretical analysis are combined. On the basis of determining the spatial movement and deformation law of overburden rock, the three-dimensional curvature, rock porosity, and fractal geometry theory were introduced to quantitatively describe the migration, stacking, and hinge characteristics of fractured rock blocks in different areas of the mining site, as well as the distribution law of rock fractures, Realized the dynamic and precise quantitative characterization of the three-dimensional structural composition and spatial occupancy of mining induced fracture fields during the mining process of steeply dipping and high mining height working faces. Research has shown that the fractured roof with steeply dipping and high mining height undergoes multi-dimensional coupled non equilibrium movement in the mining space. The middle and upper roof mainly moves vertically, while the lower roof evolves into a inclined downward movement. The form of roof failure presents three-dimensional regional differentiation along the dip, strike, and vertical directions. The upper broken rock blocks are staggered and migrated across layers to form a masonry structure. Behind the goaf, there is a “non-uniform gangue – curved cantilever beam – broken rock block” bearing structure that forms a non-uniform empty roof area. The bearing structures are constrained by each other and undergo dynamic evolution with different dip positions and overlying rock layers. The support resistance is distributed in fluctuating zones, with the middle resistance being greater than the upper and lower parts, and the strike is not synchronized with the pressure. The curvature distribution shows a “horizontal and vertical O–X” shape, and the “O” shaped internal collapsed rock blocks sink non parallel and synchronously. The inclined and anti inclined stacking structures coexist, and the positive and negative curvature sizes vary, forming weak articulated structures between the rock blocks. As the overburden layer increases, the detachment failure area shifts towards the middle and lower parts and the middle part of the goaf, and the porosity and fractal dimension of the rock mass first increase and then decrease. The research results have revealed the three-dimensional fracture movement law of the overlying rock within the goaf, enriched the control theory of the steeply dipping coal seam strata, and provided a new method for precise quantitative analysis of the movement law of the roof strata.